From the Volume‐Filling Effect to the Stress‐Bearing Network: The Reinforcement Mechanisms of Carbon Black Filler in Natural Rubber. Issue 11 (24th August 2016) - Chen, Liang; Song, Lixian; Li, Jing; Chen, Pinzhang; Huang, Ningdong; Li, Liangbin
Abstract : The reinforcement mechanism in natural rubber (NR) with added carbon black (CB) varies depending on the amount of CB filler. At low CB content, the CB effective volume fraction is below the percolation threshold of the network, so the CB simply acts as a hard filler with a volume‐filling effect for reinforcement. At high CB content, the effective volume fraction exceeds the percolation threshold; the resulting filler network transmits external stress to the entire sample, providing much reinforcement. Abstract : Using synchrotron‐radiation X‐rays for nanoscale computed tomography (X‐ray nano‐CT), the structure and corresponding reinforcement effects of carbon black (CB) filler at various amounts in natural rubber (NR) are studied during cyclic loading. All structural parameters of the CB filler, which are extracted from X‐ray images—such as the destruction and reconstruction ratios of the aggregates and the network connectivity, show a transition point with the CB content at around 30 phr (phr = parts by weight per hundred parts of rubber). When the CB content is above the transition point, the effective volume fraction exceeds the percolation threshold, and a stress‐bearing filler network can form; this network can effectively transmit the external stress to the entire sample and abruptly enhance the reinforcement factor. Below the percolation threshold, the CB filler is mainly disconnected aggregates, where its reinforcement of the rubber matrix can be mainly described by the volume‐filling effect. Using the dynamic cluster–cluster aggregation (CCA) model, calculations of the mechanical properties related to the CB content suggest that the network structure plays a major role in the reinforcement of the NR.